Care Does Not Stop Following ROSC: A Quality Improvement Approach to Postcardiac Arrest Care. Issue 2 (10th March 2021) - Pfeiffer, Stephen; Zackoff, Matthew; Bramble, Katelyn; Jacobs, Lindsey; Ruehlmann, Kristen; Stalets, Erika L.; Tegtmeyer, Ken; Dewan, Maya
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Pediatric cardiac arrests carry significant morbidity and mortality. With increasing rates of return of spontaneous circulation, it is vital to optimize recovery conditions to decrease morbidity. Methods: We evaluated all patients who presented to a large quaternary pediatric intensive care unit with return of spontaneous circulation. We compared patient-specific postcardiac arrest care preimplementation and postimplementation of a standardized postcardiac arrest resuscitation pathway. We implemented evidence-based best practices using the Translating Research into Practice framework and Plan-Do-Study-Act cycles. Our primary aim was to increase the percent of postcardiac arrest care events meeting guideline targets for blood pressure and temperature within the first 12 hours by 50% within 18 months. Results: Eighty-one events occurred in the preintervention group (August 1, 2016–April 30, 2018) and 64 in the postintervention group (May 1, 2018–December 1, 2019). The percent of postcardiac arrest events meeting guideline targets for the entirety of their postarrest period improved from 10.9% for goal mean arterial blood pressure to 26.3%, P = 0.03, and increased from 23.4% for temperature to 71.9%, P < 0.0001. Conclusions: Implementing a postcardiac arrest standardized care plan improved adherence to evidence-based postcardiac arrest care metrics, specifically preventing hypotension and hyperthermia. Future multicenter research is needed to link guideline adherence to patient outcomes.